2018
DOI: 10.1016/j.chemosphere.2017.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Diuron metabolites act as endocrine disruptors and alter aggressive behavior in Nile tilapia (Oreochromis niloticus)

Abstract: Diuron and its biodegradation metabolites were recently reported to cause alterations in plasma steroid hormone concentrations with subsequent impacts on reproductive development in fish. Since steroid hormone biosynthesis is regulated through neurotransmission of the central nervous system (CNS), studies were conducted to determine whether neurotransmitters that control hormone biosynthesis could be affected after diuron and diuron metabolites treatment. As the same neurotransmitters and steroid hormones regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 56 publications
3
24
0
Order By: Relevance
“…Insecticides can cause changes that modify the endocrine response of fish (Zhang et al, 2015). These modifications may cause deregulation on the HPI axis and promote important behavioral alterations for fish (Boscolo et al, 2018), such as changes in memory consolidation (Manuel et al, 2014;Bennion et al, 2015). Memory consolidation prepares animals to defend themselves from dangerous situations, such as predation risk (Oliveira et al, 2017), via an aversive memory (Gerlai, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Insecticides can cause changes that modify the endocrine response of fish (Zhang et al, 2015). These modifications may cause deregulation on the HPI axis and promote important behavioral alterations for fish (Boscolo et al, 2018), such as changes in memory consolidation (Manuel et al, 2014;Bennion et al, 2015). Memory consolidation prepares animals to defend themselves from dangerous situations, such as predation risk (Oliveira et al, 2017), via an aversive memory (Gerlai, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Pereira et al (2015) observed anti-androgenic effects and delayed development of male sexual organs and germ cells in Nile tilapia exposed to diuron and diuron metabolites. Indeed, Boscolo et al (2017) observed that diuron decreased testosterone levels leading to a decrease in the aggressive behavior in Nile tilapias. Thus, the effects of these two urea-derived compounds seem to act similarly, causing anti-androgenic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Diuron, another phenylurea herbicide extensively used worldwide for weed control was also found in surface waters at concentrations up to 200 ng/L in the San Francisco Bay-USA (Schlenk et al, 2012). Based on this information, studies regarding alterations in sexual hormones and gametogenesis in tilapias were previously done by our group, using 40, 100 and 200 ng/L od diuron (Pereira et al, 2015(Pereira et al, , 2016Felício et al, 2015;Boscolo et al, 2017). Therefore, tebuthiuron concentrations used in this study was chosen considering realistic tebuthiuron concentration found in natural environments but also considering other studies previously published by our laboratory with diuron, for comparative purposes.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…These estrogenic activities of Diuron and its metabolites were recently studied by Pereira et al [25] and proved that the exposure of Diuron can interfere with the normal functions of the endocrine system of fish as one of the Endocrines Disrupting Chemicals (EDCs). EDCs are a class of environmental pollutants that alter the estrogenic functions of the organism through the disruption of the estrogen receptors [26]. Additionally, the major mechanisms of endocrine disruption mentioned by Carnevali et al [27] are the EDC binding to the hormone receptor as well as the inhibition or stimulation of hormone metabolism.…”
Section: Discussionmentioning
confidence: 99%